Farmers' perceived transaction costs in relation to slaughterhouses : the case of the Swedish slaughter business - Liang, Se (SLU/Dept. of Economics, 2009)
What are the key factors driving farmers' choices of whom to sell to? This study searches for an answer. Transaction costs are hypothesized as the determinant of pig producing farmers’ choice of trading partner in this study. The farmers have a choice between two types of slaughterhouse. One of these is Scan, which used to be a farmer co-operative, but is now a so-called FCB (Farmer Controlled Business). This implies that it is fully owned by the farmers who supply their animals to the slaughterhouse. The other type of firm is IOFs (Investor-Owned Firms), which are profit maximising firms. There are many IOF slaughterhouses in the Swedish pig slaugher industry, such as Ugglarps, KLD, Dahlsjöfors, and Skövde.